2015
DOI: 10.1038/ncomms9122
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Cell migration and antigen capture are antagonistic processes coupled by myosin II in dendritic cells

Abstract: Previous work by Képiró et al. describing the photostable blebbistatin derivative para-nitroblebbistatin was inadvertently omitted from the reference list of this Article and should have been cited at instances where this inhibitor is referred to. For example, in the Results section, Képiró et al. should have been cited as follows: 'To test this hypothesis, we used a non-phototoxic form of Blebbistatin (para-nitroblebbistatin), which impairs cell migration ( Supplementary Fig. 2c) and is compatible with GFP im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 1 publication
2
10
0
Order By: Relevance
“…3 A). These experiments were performed with bone marrow-derived murine DCs (BMDCs), as previously described ( Bretou et al, 2017 ; Chabaud et al, 2015 ; Vargas et al, 2016 , 2014 ). Similar to human MDDCs, BMDCs were successfully depleted for Rab7b, and the depletion did not affect their maturation ( …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 A). These experiments were performed with bone marrow-derived murine DCs (BMDCs), as previously described ( Bretou et al, 2017 ; Chabaud et al, 2015 ; Vargas et al, 2016 , 2014 ). Similar to human MDDCs, BMDCs were successfully depleted for Rab7b, and the depletion did not affect their maturation ( …”
Section: Resultsmentioning
confidence: 99%
“…(D) Quantification of mean±s.d. speed fluctuations [calculated as s.d./mean instantaneous speed ( Chabaud et al, 2015 ; Faure-Andre et al, 2008 )]. n >150, three independent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Migration is an active process relying on actin and microtubule cytoskeleton remodeling that is accompanied with mechanical cellular changes (49). Pioneer work to address dynamics of the cytoskeleton during DC migration demonstrated that migration is dependent on nonmuscular myosinIIA contractility generating the force for movement of bone marrow-derived DCs in confined microenvironments such as microfabricated channels (50)(51)(52). Further, active remodeling of the actin cytoskeleton and its regulatory proteins is a highly dynamic process including the maturation of DCs, antigen uptake by plasma membrane vesicle internalization to endo-and lysosomal compartments, antigen processing and presentation, recycling of MHC molecules, and DC-T cell interactions at the immunological synapse (48,(53)(54)(55)(56).…”
Section: Introductionmentioning
confidence: 99%